2016
DOI: 10.1103/physreve.94.012703
|View full text |Cite
|
Sign up to set email alerts
|

Spherical nematic shells with a threefold valence

Abstract: We present a theoretical study of the energetics of thin nematic shells with two charge-one-half defects and one charge-one defect. We determine the optimal arrangement: the defects are located on a great circle at the vertices of an isosceles triangle with angles of 66• at the charge-one-half defects and a distinct angle of 48• , consistent with experimental findings. We also analyze thermal fluctuations around this ground state and estimate the energy as a function of thickness. We find that the energy of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…16(d)]. The simulation results are largely compatible with previous reports on simulations of shells in T configuration [9,[44][45][46].…”
Section: Appendix A: Explanation Of Apparent Oval Shape Of Tangentialsupporting
confidence: 89%
See 1 more Smart Citation
“…16(d)]. The simulation results are largely compatible with previous reports on simulations of shells in T configuration [9,[44][45][46].…”
Section: Appendix A: Explanation Of Apparent Oval Shape Of Tangentialsupporting
confidence: 89%
“…Even with well-defined uniform boundary conditions, there may be significant variability in the director field and distribution of topological defects in the shell. This is particularly the case for shells in a T configuration, a situation that has been extensively investigated, experimentally [5,9,13,14,29,44] as well as theoretically and by computer simulation [4,6,[8][9][10][11][44][45][46]. The Poincaré-Hopf theorem dictates that the inside as well as the outside of a T shell must have a total topological defect charge of +2 [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…1(b), regardless of the shell geometry. This cholesteric arrangement differs from its nematic counterpart, in which the triangle is not necessarily isosceles [53].…”
Section: Defect Configurations In Cholesteric Shellsmentioning
confidence: 85%
“…It has been experimentally observed that thickness variation can produce a number of novel defect configurations over a spherical liquid-crystal shell [5]. It is of great interest to include the effect of thickness in a generalized Frank free energy model to account for these new experimental observations [23]. This is beyond the scope of this study.…”
Section: Resultsmentioning
confidence: 98%